Monte Carlo Simulation As Precision Predictive Tools to Find Isodose Curve of Gamma Irradiator: A Preliminary Study - Bimo Saputro; Adhi Harmoko Saputro; Nunung Nuraeni; Heru Prasetio; Okky Agassy Firmansyah; Fendi nugroho; Hasan Mayditia (Department of Physics, Sebelas Maret University, 2024)
Dose distribution mapping is critical for guaranteeing correct sample irradiation, with both experimental and simulation methods playing important roles. Simulations are an effective way to forecast dose distribution patterns, lowering costs and increasing resource utilization. The geometry, source configuration, and measurement locations are fundamental to determine. The gamma irradiator has 48 source areas, each containing two cobalt-60 pencils measuring 8.15 cm, as well as a 4.7 cm stainless steel dummy. Alanine dosimeters were used for dose assessments, and stability varied by less than 1% over six months at 6°C and up to 5% at 50°C. The study's findings revealed a 2.25% disparity in relative dosage between experimental measurements and PHITS models. This result is a major improvement over prior research that found a 10% difference. Furthermore, dosage mapping along the XY and Z axes revealed the most uniform zone on the Z-axis, measuring 7.5 cm to 12.5 cm and with a radius of no more than 5 cm. These findings contribute to our understanding of dose distribution in gamma irradiation and highlight the utility of Monte Carlo simulations for optimizing irradiation operations. The study implies that this model can be used to improve the arrangement of cobalt-60 pencils in the irradiator, improving homogeneity and radiation outcomes.